Digital Banking and Insurance Innovation: A Study on Customer Adoption and Trust - Kanchan Shakya; Mragank Shakyawar, (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2026)
The banking industry and the insurance industry have undergone tremendous changes due to the rapid development of the digital technologies that offer new platforms to improve service efficiency, accessibility, and customer experience. The effective execution of such digital innovations however largely relies on the adoption and trust of customers. This research is cross-sectional and has a descriptive and analytical research design in order to examine customer adoption of digital banking and insurance services, evaluate customer perceptions towards digital innovation, the level of trust, and the correlation of digital innovation, customer trust, and service adoption. A structured questionnaire on a five-point Likert scale was used to gather primary data and respondents were 150 in number. The convenience sampling technique was used and the data collected were analyzed with the SPSS/MS Excel with the assistance of descriptive statistics, reliability analysis, Pearson correlation and regression analysis. The validity of the measurement scales was validated by the Alpha of Cronbach being higher than satisfactory level of 0.70. The results indicate that customers are highly adopting digital banking and insurance services and have a good perception of digital innovation. The outcome shows that there is a strong positive correlation between digital innovation and customer adoption, and digital innovation and customer trust. Moreover, regression analysis shows that customer trust is a major determinant of adoption, which interprets a large percentage of variation in the application behavior. The paper concludes that to increase the customer adoption of digital banking and insurance ecosystems, and to continue growing them, it is necessary to strengthen digital innovation and trust mechanisms.